MENGEJAWANTAHKAN NILAI TASAWUF DALAM DIRI GURU - Truli Maulida W. (Progresiva : Jurnal Pemikiran dan Pendidikan Islam, 2019)
The position of educators in the world of education has received important attention from the government. They are an important medium in the transformation of knowledge for students in particular and for the progress of the nation in general. That is, they are the bearers of socio-cultural tasks whose function is to prepare the younger generation according to the ideals of the nation. Therefore, leading people in the right direction is the formal duty of a teacher. So, every educator should have a manifestation of Sufism values in teaching students. This research paper wants to examine how to realize the values of Sufism in educators to students. Then, the goal to be achieved in this discussion is to describe the manifestation of Sufism values in the teacher / educator as a noble task. This discussion uses a descriptive method because it is limited to providing a description of a phenomenon based on library research.